Konseptualisasi Literasi Sains Mengacu pada Kerangka Sains Pisa Sejak Tahun 2000 - Khery, Yusran; Sarjan, Muhammad; Ahzan, Sukainil; Efendi, Ismail (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2022)
During the 7 rounds of PISA, Indonesian students consistently ranked low in scientific literacy assessments. In the last decade, many studies have been carried out by science education researchers in Indonesia in an effort to improve students' scientific literacy. However, this fact is contradictory to the results of the scientific literacy assessment of Indonesian students which still remains low. This can be caused by not many Indonesian science educators who understand the characteristics of scientific literacy. What are the characteristics of scientific literacy in PISA is important to understand so that teachers can apply learning oriented towards the development of scientific literacy in schools and universities. This article aims to describe the characteristics of scientific literacy referring to the PISA science framework in the period 2000-2021. This article was compiled through a literature review. Scientific literacy is defined as the ability of individuals to devote attention to science-related topics and science ideas as a form of individual reflection. A person who is scientifically literate will always devote attention to logical debates regarding science and technology that require competence: 1) explaining phenomena scientifically; 2) evaluate and design scientific investigations; and 3) interpret data and evidence scientifically. Scientific knowledge consist of content, procedural, and epistemic knowledge. The scientific literacy context consist of health and disease, natural resources, environmental quality, hazards and contamination, and the limitations of science and technology. The PISA science attitude aspect consists of a critical attitude of science in decision making and a creative attitude characterized by the ability to propose scientific ideas. In PISA 2021, scientific literacy assessment is not only present as a core domain, but also integrated with mathematical literacy, reading, and creative thinking.